A Corpus Based Study of Pluralisation of English Loan Words in Urdu - Ayesha Jamil (بازیافت, 2021)
To keep on evolving lexically is one of the significant traits of languages which renders the quality of being a living organism. Languages in this world of globalization try to serve the users in the best possible way by inclusion of new words into its lexicon whether in the form of coinages or adoption from other languages. The present study aims to identify English loanwords from the Urdu corpus and examines the process of pluralisation of English loan words in Urdu language. Through the technique of content analysis, six hundred and ninety six English loanwords were identified manually from the publicly available list of five thousand words extracted from the corpus of nineteen million tokens. The data of the corpus under study was not older than 2002. Baloch’s (2010) book, “Bunyadi Urdu Qawaid” was used to look whether the English loan words conform to the target language rules in the process of pluralisation. Results show that these loan words conform to the target language rules i.e. Urdu in the case of pluralisation. The plurals in Urdu are formed on the basis of gender so the feminine and masculine English loan words have different inflections in nominative and oblique cases just like Urdu language. This study will help the linguists to look at the similar processes in different languages that may give an insight into the nature of changes a word undergoes during the process of word borrowing. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="fals